"One of the most serious problems confronting us at present" : nurses and government hospitals in Southern Rhodesia, 1930s to 1950 (Historia, 2021)
At the centre of enquiry of this article is the nexus between the problem of the shortage of nursing personnel and provision of healthcare services in Southern Rhodesia from the mid-1930s to 1950. The article interrogates the causes of the shortage and its effects on nurses, patients and hospitals. It also investigates various responses by the Rhodesian government. I suggest that both internal and external factors were responsible for the shortage. Whereas colonial policies that were influenced by racial and gender ideologies of the day were partly responsible, equally important was Rhodesia's reliance on foreign nurses, and the Second World War which accelerated the pace of urbanisation among Africans and in the process stretched health resources in urban areas. Such an examination is significant in analysing nurses' everyday work and the provision healthcare services, and is important in exploring how the problem forced the responsible authorities to readjust the nursing policy. Efforts at improving the situation opened the way for the Rhodesian government to train African nurses. This began in 1958 and was a move that gradually transformed the structure of Southern Rhodesian Nursing Services.  Hierdie artikel handel oor tekorte aan verpleegpersoneel, en die verband tussen die probleme wat dit veroorsaak het en die verskaffing van gesondheidsdienste in Suid-Rhodesië vanaf die middel-1930's tot 1950. Daar word ondersoek ingestel na die oorsake van die tekort, en die uitwerking daarvan op verpleegsters, pasiente en hospitale. Die Rhodesiese regering se reaksie hierop kom ook onder die loep. Ek voer aan dat beide interne en eksterne faktore die tekort veroorsaak het. Koloniale beleid, wat deur die rasse- en gender-ideologieë van die tyd beïnvloed is, was deels hiervoor verantwoordelik, maar so ook Rhodesië se afhanklikheid van buitelandse verpleegsters. Die Tweede Wêreldoorlog het swart verstedeliking versnel, en sodoende gesondheidshulpbronne in stedelike gebiede onder druk geplaas. Dit is belangrik om hierdie elemente van nader te bekyk, ten einde verpleegsters se alledaagse werk en die verskaffing van gesondheidsdienste te ontleed. Dit is ook belangrik om vas te stel hoe die probleem die owerhede genoop het om verpleeg- beleid aan te pas. Pogings om die situasie te aan te spreek het die weg gebaan vir die opleiding van swart verpleegsters. Dit het in 1958 'n aanvang geneem en het mettertyd die struktuur van die Suid-Rhodesiese Verpleegdienste omvorm.
Keywords: Southern Rhodesia; Tekort aan verpleegsters; Provision of health services; Shortage of nurses; Verskaffing van gesondheidsdienste